Effects of clamp width on vibration features of fuel pipeline of aero-engine. (20th December 2021) - Zhang, Xingsheng; Cheng, Guanbing; Tian, Jing
The fuel delivering pipeline for aero-engine plays an important role during the combustor burning, engine control and regulation to make the engine in good operation condition. Therefore, understanding the vibration features of the pipelines is of interest during pipeline design and distribution. The paper established physical models of fuel pipelines with different widths of the clamps. The pipeline resonant frequencies, vibration modes and displacement amplitudes along three directions were obtained by means of finite element method accordingly. The effects of the clamp widths were analysed on those modal parameters by linear static analysis and modal analysis. The results show that the pipeline vibration frequency increases with vibration orders and also shows cluster characteristics. The linear static and modal analysis reveals similar tendencies. The clamp width increases the pipeline stiffness and improves its vibrating frequency. Besides, the vibration shapes revolve due to the symmetric structure of the fuel pipelines.